Efektifitas Penyelenggaraan E-Puskesmas Di Puskesmas Lubuk Buaya Kota Padang ¬ - Putri, Shilvia Apriyani; Syamsir, Syamsir (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research was done in Puskesmas Lubuk Buaya Padang City whichpurpose to discover about to effectiveness of organized e-puskesmas in Puskesmas Lubuk Buaya Padang City. This research applies a descriptive qualitative method, namely a method by providing a comprehensive description of the research. Informants selection of informants in this reseacrhusing purposive sampling technique. Prosess of aggregation data colth pass through observation technique, study documentation and interviews, while technique for validity testing data that using resource triangulation with data analysis such as a data collection, data reduction, data presentation, along with pulling conclusions. The results of the research conducted by researchers was explain effectiveness of organized e-puskesmas in puskesmas Lubuk Buaya Padang City was not yet effective, because in case still presence obstacle inside administration that e-puskesmas, that e-puskesmas namely network problems are not always good, sometimes disconnected when used so that it can slow down patient services in medical treatment, and other obstacles, sometimes the patient data input report for each clinic is also done manually till case mentioned needed much time in data in data input medical patient and be able pulling conclusion its not yet effective organized e-puskesmas in that Lubuk Buaya.